2004
DOI: 10.1073/pnas.0308126101
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Notch signaling in hippocampal synaptic plasticity

Abstract: During development of the nervous system, the fate of stem cells is regulated by a cell surface receptor called Notch. Notch is also present in the adult mammalian brain; however, because Notch null mice die during embryonic development, it has proven difficult to determine the functions of Notch. Here, we used Notch antisense transgenic mice that develop and reproduce normally, but exhibit reduced levels of Notch, to demonstrate a role for Notch signaling in synaptic plasticity. Mice with reduced Notch levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(190 citation statements)
references
References 42 publications
7
181
2
Order By: Relevance
“…Levels of basal and stimulation-induced NF-jB activity were significantly decreased in mice with reduced Notch levels. 28 Constitutive levels of Notch activity are essential to maintain NFjB activity in various cell types. Notch and NF-jB pathways are key regulators of numerous cellular processes such as proliferation, differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of basal and stimulation-induced NF-jB activity were significantly decreased in mice with reduced Notch levels. 28 Constitutive levels of Notch activity are essential to maintain NFjB activity in various cell types. Notch and NF-jB pathways are key regulators of numerous cellular processes such as proliferation, differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…5). Because NF-B pathways are key regulators of numerous cellular processes such as proliferation, differentiation, and inflammation, our results clearly provide molecular evidence for potential crosstalk between Notch-1 and NF-B pathways and suggest that cell growth inhibition and apoptosis promoted by the downregulation of Notch-1 after treatment of rhamnetin and cirsiliol may be partly mediated by NF-B (73)(74)(75). Because an approach using Notch-1 siRNA is not yet practical for therapeutic purposes, we recommend the use of rhamnetin and cirsiliol found to be potent agents capable of regulating NF-B pathway by Notch-1 inhibition.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, FE65 also interacts with the intracellular domain of Notch, and it has been suggested that Notch and APP may regulate a number of same target genes (Fischer et al 2005). Mice with a reduced level of Notch display defects in both LTP and spatial learning (Costa et al 2003;Wang et al 2004b). Because certain regulatory functions may be shared by FE65s (FE65, FE65L1, and FE65L2), using neurons derived from double-or triple-mutants will facilitate the understanding of how the FE65 family participates in the complex signaling network.…”
Section: Discussionmentioning
confidence: 99%